Digital public space, disputes and violence: comments on two Argentine LGBTIQ blogs - Pérez Riedel, Magalí Daniela (Universidad de Chile. Instituto de la Comunicación e Imagen, 2018)
In this article, we outline an analytical reflection on the territorial disputes that take place between 2012 and 2015 in the comments sections of the Argentine blogs Tod@s and Boquitas pintadas, where sex-gender diversity issues are addressed. We conducted a theoretical-conceptual approach from Latin American cultural studies and Internet studies with a feminist and queer perspective. Our work focuses on a corpus of 5,095 comments that is analyzed with a qualitative methodological strategy. We inquire about the meanings about spatial appropriations and disputes about users’ sense of belonging with respect to these blogs.